Code-Switching and Code-Mixing Strategies in Multilingual Family Communication on the Ueno Family Japan YouTube Content - Kafifah Ayu Lestari; Rosita Sofyaningrum (Universitas Suryakanca, 2026)
Abstract This study aims to describe the forms of code-switching and code-mixing and to analyze their use as language strategies in the YouTube channel Ueno Family Japan. A qualitative descriptive method was employed through video observation and detailed utterance recording. The findings reveal that code-switching and code-mixing are consciously used to adapt language for the audience, assert the family’s multicultural identity, foster emotional closeness, and enhance communication effectiveness. Code-switching mainly occurs inter-sententially and via tag insertions, while code-mixing appears as foreign words inserted into Indonesian sentences. These findings suggest that code-switching and code-mixing are not merely linguistic phenomena but functional and adaptive communicative strategies in multilingual family interactions on digital platforms.